Piracy : - Adrian Johns. (The University of Chicago Press)
A general history of the pirates -- The invention of piracy -- The piratical enlightenment -- Experimenting with print -- Pharmaceutical piracy and the origins of medical patenting -- Of epics and orreries -- The land without property -- Making a nation -- The printing counterrevolution -- Inventors, schemers, and men of science -- International copyright and the science of civilization -- The first pirate hunters -- The great oscillation war -- Intellectual property and the nature of science -- The pirate at home and at large -- From phreaking to fudding -- Past, present, and future.